Marx’s model of development of society – contemporary challenges - Chipev, Plamen (Research Papers, 2018)
The paper aims to project Marxian model for progress of the society over the actual evidence from the present day developed economies in order to assess its adequacy, avoiding the ideological controversies as much as possible. Results from the original study show certain degree of adequacy – the basic difference and contradiction between the social strata are preserved and even aggravated through the deepening economic inequality. Two of the analyzed three variants of resolving the controversy are also congruent with the basic features of the Marxian model.